Development of Android-based E-Modules on Molecular Shape Materials of VSEPR Theory - Wandi Wandi; Eny Enawaty; Rini Muharini; Rodi Putra Sartika (JURNAL EKSAKTA PENDIDIKAN (JEP), 2023)
The use of teaching materials in online learning during the Covid-19 pandemic results in a lack of students' understanding of the molecular shape material of the VSEPR theory leading to learning objectives not being achieved. So the researchers make an Android-based e-module as a teaching material as a solution so that students better understand the material of molecular shapes in online learning. This study aims to determine the feasibility of an android-based e-module on the molecular shape material of the VSEPR theory. This research used a research and development (R&D) method which is based on the ADDIE model. The android-based e-module on the molecular shape material of the VSEPR theory was validated by an expert or validator which included the feasibility of the material, language, and graphics. The results show that the android-based e-module developed is categorized as very feasible to use. This Feasibility is reviewed from the results of the validation of the feasibility of the material which obtain a validity score of 92.69% showing that the e-emodule made has fulfilled the Feasibility aspects including the suitability of the material and basic competence, the accuracy of the material, the updating of the material, and encouraging curiosity. Language Feasibility validation with a validity score of 92.69% shows the module made has fulfilled the Feasibility aspects of being straightforward, communicative, conformity with the development of students, and conformity with the correct rules of the Indonesian language. Graphic feasibility validation with a feasibility percentage of 91.66% with very decent criteria shows that the e-module has met the qualifications from the aspect of measurement, cover design, and cover body design. The feasibility research results obtained will be applied as a reference in the manufacturee-mode android based, so the e-modules that are suitable for use can be used in further research